2015
DOI: 10.1007/s00134-015-3906-y
|View full text |Cite
|
Sign up to set email alerts
|

The Surviving Sepsis Campaign bundles and outcome: results from the International Multicentre Prevalence Study on Sepsis (the IMPreSS study)

Abstract: Compliance with all of the evidence-based bundle metrics was not high. Patients whose care included compliance with all of these metrics had a 40% reduction in the odds of dying in hospital with the 3-h bundle and 36% for the 6-h bundle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
227
8
13

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 349 publications
(264 citation statements)
references
References 31 publications
16
227
8
13
Order By: Relevance
“…This benefit has also been shown across a wide geographic spectrum. A study of 1794 patients from 62 countries with severe sepsis (now termed "sepsis" after the Sepsis-3 definition [1] or septic shock demonstrated a 36-40% reduction of the odds of dying in the hospital with compliance with either the 3-or 6-h SSC bundles [48]. This recommendation met the prespecified criteria for a BPS.…”
Section: We Recommend That Hospitals and Hospital Systems Have A Perfmentioning
confidence: 96%
“…This benefit has also been shown across a wide geographic spectrum. A study of 1794 patients from 62 countries with severe sepsis (now termed "sepsis" after the Sepsis-3 definition [1] or septic shock demonstrated a 36-40% reduction of the odds of dying in the hospital with compliance with either the 3-or 6-h SSC bundles [48]. This recommendation met the prespecified criteria for a BPS.…”
Section: We Recommend That Hospitals and Hospital Systems Have A Perfmentioning
confidence: 96%
“…A 7.5-year study conducted in 218 centers in USA, South America, and Europe demonstrated that increased compliance with sepsis performance bundles was associated with a reduction in the mortality rate (18). Another investigation conducted in 62 countries also showed that patients with severe sepsis whose care included compliance with all the metrics of the 3 h bundle, and 6 h bundle had 40% and 36% reduction in hospital mortality, respectively (19). A multicenter observational study conducted from September 2007 to October 2008 in 11 ICUs of Chinese teaching hospitals showed that the overall compliance during 6 h resuscitation and 24 h management bundles were 5.5% and 17.4%, respectively (20).…”
Section: Mortality Of Sepsismentioning
confidence: 99%
“…Greater attention should be given to infected and septic patients without organ dysfunction who may benefit from prompt diagnosis and treatment. It is the early application of the Surviving Sepsis Campaign Bundles of Care that has improved outcomes [15].…”
Section: The Uglymentioning
confidence: 99%